2015
DOI: 10.1111/hsc.12202
|View full text |Cite
|
Sign up to set email alerts
|

Care arrangements for community-dwelling people with dementia in Germany as perceived by informal carers - a cross-sectional pilot survey in a provincial-rural setting

Abstract: The majority of people with dementia live at home, and informal carers assume the role of key care providers, often supported by formal services. The purpose of this pilot study was to assess home-based care arrangements, to illustrate utilisation of formal services over time and to identify factors associated with perceived stability of the care situation from the informal carer's perspective. A self-administered questionnaire (D-IVA 'Instrument for Assessing Home-Based Care Arrangements for People with Demen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 42 publications
(69 reference statements)
3
30
1
1
Order By: Relevance
“…Most studies also reported a higher proportion of female compared to male participants with dementia, as would be expected based on the higher prevalence of dementia among women (Prince et al, 2015). Few studies (Arai, Sugiura, Miura, Washio, & Kudo, 2000;Edelman, Kuhn, Fulton, & Kyrouac, 2006;Forbes, Morgan, & Janzen, 2006;Herron & Rosenberg, 2017;Li, Kyrouac, McManus, Cranston, & Hughes, 2012;McDonnell & Ryan, 2014;Nordberg, von Strauss, Kåreholt, Johansson, & Wimo, 2005;Sanders & McFarland, 2002;von Kutzleben, Reuther, Dortmann, & Holle, 2016) examined sex (biological status as male or female) or gender (the ways maleness or femaleness may be expressed through roles, behaviors, etc.) in relation to service needs, use, and barriers.…”
Section: Idenɵficaɵonmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies also reported a higher proportion of female compared to male participants with dementia, as would be expected based on the higher prevalence of dementia among women (Prince et al, 2015). Few studies (Arai, Sugiura, Miura, Washio, & Kudo, 2000;Edelman, Kuhn, Fulton, & Kyrouac, 2006;Forbes, Morgan, & Janzen, 2006;Herron & Rosenberg, 2017;Li, Kyrouac, McManus, Cranston, & Hughes, 2012;McDonnell & Ryan, 2014;Nordberg, von Strauss, Kåreholt, Johansson, & Wimo, 2005;Sanders & McFarland, 2002;von Kutzleben, Reuther, Dortmann, & Holle, 2016) examined sex (biological status as male or female) or gender (the ways maleness or femaleness may be expressed through roles, behaviors, etc.) in relation to service needs, use, and barriers.…”
Section: Idenɵficaɵonmentioning
confidence: 99%
“…When examining specific support services, those involving direct assistance to the person with dementia (e.g., help with activities of daily living or home care) and home maintenance were used most frequently (Arai et al, 2000;Burholt, Wenger, & Scott, 1997;Ervin & Reid, 2015;Forbes et al, 2012;Forbes et al, 2006;von Kutzleben et al, 2016;Sun et al, 2007;Wenger et al, 2002). Reported use of support/self-help groups by caregivers and people with dementia was quite low, ranging from 4.8 per cent to 25 per cent (Buettner & Langrish, 2001;Ervin & Reid, 2015;Forbes et al, 2006;Innes et al, 2003;Sun et al, 2007).…”
Section: Education and Support Service Needs Availability And Usementioning
confidence: 99%
“…Today, older persons are increasingly expected to manage their own health care and life (Hengelaar et al, ). This emphasis on self‐management fits the policy trend in many western European countries to reduce institutionalised secondary care and encourage older persons to live at home for as long as possible in order to contain excessively growing healthcare costs (Broese van Groenou, Jacobs, Zwart‐Olde, & Deeg, ; Dahlberg, Demack, & Bambra, ; Kutzleben, Reuther, Dortmann, & Holle, ; Wittenberg, Kwekkeboom, Staaks, Verhoeff, & Boer, ). Self‐management can be defined variously (Barlow, Wright, Sheasby, Turner, & Hainsworth, ; van Hooft, Dwarswaard, Jedeloo, Bal, & van Staa, ).…”
Section: Introductionmentioning
confidence: 79%
“…The quantitative data used in the mixed-methods approach were based on items extracted from two standardized questionnaires used within the DemNet-D study [ 17 , 19 ]. These items were drawn from the “Berlin Inventory of Caregivers” (BIZA-D) [ 20 ] and the “Instrument for Assessing Home-Based Care Arrangements for People with Dementia” (D-IVA) [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The ordinal-scaled items were analyzed using the Mann–Whitney U Test because the sample data were not normally distributed. The findings were compared against the data from another project that focused only on PwD in the community [ 21 ] without considering DCNs. A statistical analysis was performed using the SPSS 19 software package [ 28 ].…”
Section: Methodsmentioning
confidence: 99%